Triple Non-Statin Therapy with Ezetimibe, Inclisiran, and Bempedoic Acid in Patients with Genetically Confirmed Statin-Induced Rhabdomyolysis: A Dual Case Report - Jozef Dodulík; Jiří Plášek; Ivana Kacířová; Romana Uřinovská; Jiří Vrtal; Jan Václavík (Pharmaceuticals, 2025)
Background: Statin intolerance is a serious therapeutic dilemma in secondary cardiovascular prevention (e.g., ESC/EAS Guidelines 2023). This is especially true when confirmed by genetic predisposition and complicated by rhabdomyolysis. Although several non-statin agents have become available in recent years, evidence regarding their combined use in high-risk statin-intolerant patients remains limited. Furthermore, the pharmacokinetics of statins in toxic concentrations are poorly characterized in clinical settings. Case Presentation: We present two cases of genetically confirmed statin-induced rhabdomyolysis, both accompanied by severe acute kidney injury requiring renal replacement therapy. In both patients, serial measurements of rosuvastatin plasma concentrations revealed markedly delayed elimination, with detectable levels persisting for several weeks despite ongoing dialysis. Estimated half-lives exceeded 7 days in both cases, far beyond the known therapeutic range. Genetic testing identified SLCO1B1, ABCB1, and CYP2C9 polymorphisms linked to reduced hepatic uptake and impaired drug clearance. Following biochemical recovery, both patients were initiated on a triple non-statin lipid-lowering regimen consisting of ezetimibe, bempedoic acid, and inclisiran. The combination was well tolerated, with no recurrence of muscle-related symptoms or biochemical toxicity. LDL-C levels were reduced from 3.05 to 1.59 mmol/L and from 4.99 to 1.52 mmol/L, respectively, with sustained response over 12 and 40 weeks. Full lipid profiles demonstrated favorable changes across all parameters. Conclusions: These two cases suggest that the combination of ezetimibe, inclisiran, and bempedoic acid may serve as a safe and effective therapeutic option in patients with severe statin intolerance. Pharmacogenetic testing and serial pharmacokinetic assessment may guide personalized lipid-lowering strategies and improve outcomes in this challenging patient population.